Invasion of the body snatchers - Grant, Barry Keith; British Film Institute ([New York] : Palgrave Macmillan ; London : British Film Institute, 2010)
"Upon its release in 1956, Don Siegel's Invasion of the Body Snatchers was commonly perceived as another B-thriller in the cycle of science fiction and horror films that proliferated at the time. But in the 50 years since, its reputation has grown from cult status to become an acknowledged classic of American cinema. In the first comprehensive critical study of the film, Barry Keith Grant traces the film's historical context, it appeared in an America gripped by Cold War paranoia and atomic anxieties, and its production history, and goes on to explore the importance of genre, Communism, conformity, modernity, post-War society, and gender for an understanding of the film's cultural contexts and metaphorical weight"--
Machine generated contents note: Acknowledgements -- Historical context -- Contemporary Hollywood -- Production history -- Genre -- Don Siegel, director -- Communism and conformity -- Modernity and postwar society -- Gender -- Conclusion.
Bibliografija
Keywords: Invasion of the body snachers (Motion picture : 1956); Siegel, Don -- Invazija tjelokradica; znanstveno-fantastični film